You are on page 1of 9

Chapter 1

Dynamical Model for
Wideband DOA Estimation
October 28, 2014

1.1

Source motion model

˙
Consider a sensor array having N sensors. Let θ(t) and θ(t)
be the angle and angular rate of a wideband source. The state
vector x(t) as  

θ(t)
x(t) =
(1.1)
˙
θ(t)
The model of the source is given as follows

x(t + 1) = Ax(t) + w(t) 

here A = 
2 

σw 1 0
0 σw2 2

1 T
0 1

(1.2) 

and w(t) ∼ N (02×1 , Σw ) where Σw =

1

1.2

Measurement Equations

Figure 1.1: Signal arriving at the sensor which is located at [pxn

p yn ]

From the Figure 1.1 , the output of the nth sensor of the
array can be written as
zn (t) = s0 (t − τn (θ(t))) + n (t)

(1.3)

where , c is the speed of wave propagation,
(pxn − px0 ) cos θ(t) + (pyn − py0 ) sin θ(t)
τn (θ(t)) =
(1.4)
c
is the delay corresponding to source and the nth sensor located
at pn = [pxn pyn ] , s0 (t) is called the reference signal which is
2

the signal arriving at the reference point p0 = [px0 py0 ] of the
array and n (t) ∼ N (0, σ2n ) is the measurement noise.
The reference point p0 , is chosen to coincide with the location
of the origin of the co-ordinate systems, so that p0 = [0 0],
From 1.4, the delay can be written as
pxn cos θ(t) + pyn sin θ(t)
c   

x(t)
1
=
pxn − px0 pyn − py0
y(t)
c 

1
pxn pyn x(t)
=
c

τn (θ(t)) =

1.2.1

(1.5)

Taylor expansion

Now consider the function in 1.3 ie s0 (t − τn (θ(t)) (for array
processing, τn (θ(t)) is relatively small value less than unity), it
can be expanded using the Taylor series as
s0 (t − τn (θ(t))) = s0 (t) + τn (θ(t))s˙ 0 (t) + ∆n (t)

(1.6)

where ∆n (t) is the higher order terms of Taylor expansion.
Using 1.6 in 1.3 gives
zn (t) = s0 (t) + τn (θ(t))s˙ 0 (t) + ∆n (t) + n (t)
= s0 (t) + τn (θ(t))s˙ 0 (t) + ˜n (t)

(1.7)
(1.8)

where ˜n (t) = ∆n (t) + n (t).
Thus the output of the each sensor can be written as
z1 (t) = s0 (t) + τ1 (θ(t))s˙ 0 (t) + ˜1 (t)
z2 (t) = s0 (t) + τ2 (θ(t))s˙ 0 (t) + ˜2 (t)
..
.
zN (t) = s0 (t) + τN (θ(t))s˙ 0 (t) + ˜N (t)
3

(1.9)

1.2.2

Estimating s0 (t) and s˙ 0 (t) using Maximum Likelihood (ML) method

Assumption: Measurements in the sensors at a given time
are independent i.e. at t = ti , the measurements z1 , z2 . . . zN
are independent and the noise is Gaussian
Using 1.9, the measurement equations can be written as
z1 = s0 + τ1 (θ)s˙ 0 + ˜1
z2 = s0 + τ2 (θ)s˙ 0 + ˜2
..
.
zN = s0 + τN (θ)s˙ 0 + ˜N

(1.10)

Assume z1 , z2 . . . zN be random variables, whose probability
density
(pdf) , parametrized by the unknown quantities
 function

s0
s =  s˙ 0  is given by
θ
p(z1 ; s) ∼ N (µz1 , σ˜21 )
p(z2 ; s) ∼ N (µz2 , σ˜22 )
..
.
p(zN ; s) ∼ N (µzN , σ˜2N )

(1.11)

where µzn = s0 + τn (θ)s˙ 0 and cov(˜n ) = σ˜2n .
Since the random variables are assumed to be independent,
the joint pdf is given as

4

p(z; s) = p(z1 ; s) × p(z2 ; s) . . . p(zN ; s)
1
1
T −1
= N/2 N/2 e− 2 (z−µ) Σ (z−µ)
2π |Σ|
∼ N (µ, Σ)

(1.12)
(1.13)





z1
µz1
σ˜21 0 . . . 0
 z 
 µ 
 0 σ2 . . . 0
 2 
 z2 
 
˜2
where z =  .. , µ =  ..  and Σ = 
..
 . 
 . 

.
zN
µzN
0 0 . . . σ˜2N
The negative log-likelihood (ignoring constants) is given by

1
L = (z − µ)T Σ−1 (z − µ)
2
N
1 X (zn − µzn )2
=
2 n=1
σn2





(1.14)
(1.15)

Estimation of s0 (t)

Assumption: σ˜21 = σ˜22 = · · · = σ˜2N = σ 2
Taking the derivative w.r.t. s0 (t) and equating to zero gives
N
X
∂L
∂µzn
= 0 = ( (zn − µzn ))
∂s0
∂s0
n=1

(1.16)

∂(s0 + τn (θ)s˙ 0 )
∂µzn
=
=1
∂s0
∂s0

(1.17)

Here

5

this gives
N

X
∂L
=0=
(zn − s0 − τn (θ)s˙ 0 )
∂s0
n=1
=

N
X

zn − N s0 − s˙ 0

n=1

N
X

τn (θ)

(1.18)

n=1

The above equation yields

sˆ0 = z¯ − s˙ 0 τ¯(θ)

where z¯ =

PN

n=1 zn

N

and τ¯(θ) =

(1.19)

PN

n=1 τn (θ)

N

Estimation of s˙ 0 (t)

Assumption: σ˜21 = σ˜22 = · · · = σ˜2N = σ 2
Taking the derivative w.r.t. s˙ 0 (t) and equating to zero gives
N
X
∂µzn
∂L
= 0 = ( (zn − µzn ))
∂ s˙ 0
∂ s˙ 0
n=1

(1.20)

∂µzn
∂(s0 + τn (θ)s˙ 0 )
=
= τn (θ)
∂ s˙ 0
∂ s˙ 0

(1.21)

Here

6

this gives
N

X
∂L
=0=
(zn − s0 − τn (θ)s˙ 0 )τn (θ)
∂ s˙ 0
n=1
=
=

N
X
n=1
N
X

zn τn (θ) − s0

N
X

τn (θ) − s˙ 0

n=1

N
X

τn2 (θ)

(1.22)

n=1

zn τn (θ) − s0 N τ¯(θ) − s˙ 0 N τ¯2 (θ)

(1.23)

n=1

this gives

sˆ˙0 =

where τ¯2 (θ) =

PN

n=1 zn τn (θ)
N τ¯2 (θ)

s0 τ¯(θ)
− ¯2
τ (θ)

(1.24)

PN

2
n=1 τn (θ)

N

Estimation of θ

Assumption: σ˜21 = σ˜22 = · · · = σ˜2N = σ 2
Taking the derivative w.r.t. θ and equating to zero gives
N
X
∂L
∂µzn ∂τn (θ)
= 0 = ( (zn − µzn ))
∂θ
∂τn (θ) ∂θ
n=1

∂(s0 + τn (θ)s˙ 0 )
∂µzn
=
= s˙ 0
∂τn (θ)
∂τn (θ)
∂µzn
px − sin θ + pyn cos θ
= τ˙n (θ) = n
∂τn (θ)
c
7

(1.25)

(1.26)
(1.27)

1.2.3

Measurement Model

Using 1.5 the differential measurement signals can be written as
1
c
1
z2 (t) = s0 (t) +
c
..
.
1
zN (t) = s0 (t) +
c
z1 (t) = s0 (t) +

px 1

py1 

x(t)s˙ 0 (t) + ˜1 (t)

px 2

py2 

x(t)s˙ 0 (t) + ˜2 (t)

px N

pyN 

x(t)s˙ 0 (t) + ˜N (t)

(1.28)

The above set of equation can be expressed in matrix form as

∆z(t) =s˙ 0 (t)Px(t) + ˜(t)



where ∆z(t) = 

and

z1 (t) − s0 (t)
z2 (t) − s0 (t)
..
.
zN (t) − s0 (t)

(1.29)

px1 py1
 p

 x2 py2

 , P = 1c 
..


.
pxN pyN





 

˜1 (t)
 ˜ (t) 
 2
 
˜ =  .. 
 .  
˜N (t)
Now the source and measurement equation can be summarized as

8

x(t + 1) =Ax(t) + w(t)
∆z(t) =s˙ 0 (t)Px(t) + ˜(t)

9

(1.30a)
(1.30b)